Geometry modulated upconversion photoluminescence of individual NaYF4: Yb3+, Er3+ microcrystals - Bing Wang; Jiao Wang; Yongfeng Mei (AIP Advances, 2017)
Upconversion (UC) photoluminescence (PL) properties of individual β-NaYF4: Yb3+, Er3+ microcrystals are investigated on their crystal orientation and size by a confocal micro-photoluminescence (μ-PL) system. The UC PL intensities including red and green bands of individual microcrystals change nearly lineally with their diameter but in different slopes. The ratio of integrated PL intensities between red and green bands (R/G) of individual microcrystals can be modulated by the crystal geometry, which is attributed to the optical propagation path and optical loss coefficient α. PL emission mapping along the crystal surface reveals a typical characteristic of optical waveguide in our UC microcrystals. Importantly, the variation of anisotropy in (100) and (001) crystal plane influences the UC PL spectra in the single microcrystals. Our finding could help the basic understanding of UC luminescence in micro/nanocrystals and hint their optimized fabrication for enhanced light emission.